2021
DOI: 10.3390/ma14051157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tool Geometry and Process Parameters on the Properties of Friction Stir Spot Welded Multiple (AA 5754 H111) Aluminium Sheets

Abstract: Friction stir spot welding is an emerging spot-welding technology that offers opportunities for joining a wide range of materials with minimum energy consumption. To increase productivity, the present work addresses production challenges and aims to find solutions for the lap-welding of multiple ultrathin sheets with maximum productivity. Two convex tools with different edge radii were used to weld four ultrathin sheets of AA5754-H111 alloy each with 0.3 mm thickness. To understand the influence of tool geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Material outflow is a common defect [24,35,55]. The amount of outflow is associated with the shape of the pin and the process parameters [17,21,24]. A comparison of the CR6 and TR5 joints made with equal parameters of 475 mm/min and 475 rpm revealed that the TR5 joint showed no material outflow while the CR6 showed a significantly greater amount of it, especially at the beginning of the joint (Figure 3a,c).…”
Section: Comparison Of the Tool Pin's Shapementioning
confidence: 99%
See 1 more Smart Citation
“…Material outflow is a common defect [24,35,55]. The amount of outflow is associated with the shape of the pin and the process parameters [17,21,24]. A comparison of the CR6 and TR5 joints made with equal parameters of 475 mm/min and 475 rpm revealed that the TR5 joint showed no material outflow while the CR6 showed a significantly greater amount of it, especially at the beginning of the joint (Figure 3a,c).…”
Section: Comparison Of the Tool Pin's Shapementioning
confidence: 99%
“…Zlatanovic et al [17] compared the effect of different rotational speeds on joints made with Friction Stir Spot Welding. It was stated that for the AA5754-H111 aluminium alloy, higher mechanical properties were obtained at lower rotational speeds (1000-1500 rpm).…”
Section: Introductionmentioning
confidence: 99%
“…The materials flow in the FSW joining process is the consequence of materials velocity and heat generation during the stirring action of the FSW tool [58][59][60][61]. Due to a better understanding of thermo-mechanical outputs and relation with materials velocity results with the actual situation, it is necessary to investigate the surface flow of FSW joints.…”
Section: Flow Of Materialsmentioning
confidence: 99%
“…In 1991, friction stir welding (FSW) was initially introduced by TWI in the United Kingdom as a newly developed solid-state welding process, particularly for joining aluminum alloys with specific requirements that should be fulfilled [1,2]. Then friction stir spot welding (FSSW) was developed as one of its variant for local joining of similar and dissimilar sheets [3][4][5][6][7][8][9] as a promising technique with similarities to the basic concepts of linear FSW with a specific requirement where no lateral movement of the tool is required [10]. More interestingly, the rotating tool pierces the sheets that are being welded and then produces a stir zone.…”
Section: Introductionmentioning
confidence: 99%